Marketing Strategies to be Adopted by the Garment Exporters after the Quota Removal in Tirupur - Karthikeyan, G. B.; Ramachandran, A. (Indian Journal of Marketing, 2009)
India is one of the world's ten largest exporters of textiles and clothing, and relies heavily on exports to sustain its industry. The export markets (about 65%) mainly cater to the Untied States of America (USA) and the European Union. The remaining of India's exports is spread over a number of quota countries, especially the UAE, Japan and the former Soviet Republic. India's share in the global textile and clothing market in the last decade did not grow much because of quantitative restriction on exports to the US, the EU and Canada, because of not being a member of important preferential trade agreements and because of having a lesser degree of export competitiveness than its competitors. With the abolition of quota system, the competition among developing countries for gaining export share or retaining it will depend to a great extent on the competitiveness of the country's textile and clothing sector. This study currently focuses on the issues to be concentrated upon by the Tirupur Exports to face quota removal. The complete elimination/phase-out of export quota's has brought to sharp focus, the weakness of India garment export industry as well as the exciting opportunities to carve out an ambitious but achievable share in the global clothing imports. The jockeying for position among current competitors will be determined by the forces governing competition. In the race for being ahead of competition, "sustainable competitive advantage" is central to the strategy. Sustainable advantage depends on three aspects: a) Size in the target market - it culminates in the expansion of marketing, establishing brand name for products, taking into account the market selection strategy adopted by the buyers. b) Superior access to resources-this may probe into the insights of sourcing decisions. The orders from the buyers now-a-days are more dynamic-it not only includes the value addition but also fabric texture to be imported from different places, and the promotional avenues which has to be concentrated to meet it's own competitors. c) Driving strategies to win markets-which needs immediate focus on uplifting the technology, increasing the investment capacity at the level need, paying attention towards high quality supply chain management and removing the investment bottle necks which tamper the export market to the maximum extent.